Integration Children Behavioral Education According To Luqman And Ulwan Najati - Nur Azwani Mansor @ Noordin; Shahnun Musa; Khairulnazrin Nasir (Rabbanica: Journal of Revealed Knowledge)
The formation of commendable attitudes, behavior and morals needs to be cultivated from an early age by the people who are closest to the children. Parents, families, guardians and teachers are responsible for educating and shaping children's behavior, because of the closeness factor and the strongest influence on children. Therefore, this study aims to describe the main methods of education, teaching and learning behaviour towards the formation of commendable values and morals towards children. The approach is discussed from the perspective of famous scholars Abdullah Nasih ‘Ulwan and Muhammad Utsman Najati. This study applies a qualitative research approach with the theme of literature review. Data is obtained from scientific articles and books. The method of content analysis by synthesis is applied to the education method of Abdullah Nasih ‘Ulwan from his work Tarbiyat al-Awlad fi al-Islam and the learning method of Muhammad Uthman Najati from his work Al-Qur'an wa ‘Ilm An Nafs and al-Hadith al-Nabawi wa Ilm an-Nafs as well as from surah Luqman in the al-Quran to discuss value education in behaviour. The results of the study found that the education method in Surah Luqman, Abdullah Nasih ‘Ulwan and the psychological learning method of Muhammad Ustman Najati can be integrated to form a simple and practical behavioural education for parents and guardians. The implication is that the method is seen to be very effective in treating children in line with Islamic Shari'a because it is based on the teachings of the Quran and Hadith, and is even streamlined with the views of contemporary Islamic scholars that are in line with the reality of today.